Apropierea și întârzierea parousiei la părinții ante- și post-niceeni – partea a II-a - Laurențiu Moț (TheoRhēma, 2016)
The concepts of the nearness and delay of parusia in the thought of the ante- and post-Nicene Fathers, dealt with in part one, have here been taken up again, this time with a focus on the way the Nicene and post-Nicene Fathers related to the nearness and delay of Christ’s return. In the context of a Christianized Roman Empire, the arguments for nearness decreased, whereas the reasons for delay increased. Thus, after Nicaea it was believed that the end is near for reasons, such as, the testimony of Scripture, the signs of the times, and personal hardships. The delay was envisioned due to realities and ideas such as the Christianized Rome, the millennium as the Church Era, the failure of the signs of the times, the grace for sinners, and the necessity for the maturation of the conflict between good and evil.